2018
DOI: 10.1186/s12888-018-1746-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient care activities by community pharmacists in a capitation funding model mental health and addictions program

Abstract: BackgroundCommunity pharmacists are autonomous, regulated health care professionals located in urban and rural communities in Canada. The accessibility, knowledge, and skills of community pharmacists can be leveraged to increase mental illness and addictions care in communities.MethodsThe Bloom Program was designed, developed, and implemented based on the Behaviour Change Wheel and a program of research in community pharmacy mental healthcare capacity building. We evaluated the Bloom Program as a demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…A good, long-term relationship between pharmacist and patient was cited as a mechanism to achieve resolution of problems related to mental health and medication in a mental health and addictions programme in Nova Scotia (Bloom Program). The private consultation room was the main location for these discussions [19]. In the UK, despite the requirement for a private consultation rooms in the community pharmacy contract, patients are often unaware that this facility is available [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good, long-term relationship between pharmacist and patient was cited as a mechanism to achieve resolution of problems related to mental health and medication in a mental health and addictions programme in Nova Scotia (Bloom Program). The private consultation room was the main location for these discussions [19]. In the UK, despite the requirement for a private consultation rooms in the community pharmacy contract, patients are often unaware that this facility is available [20].…”
Section: Discussionmentioning
confidence: 99%
“…There have been recommendations for follow-up and monitoring in MURs [25]. The Bloom Program, previously described [19], could fit this specification from a mental health perspective. However, this would require remuneration, something seen as a barrier by participants.…”
Section: Discussionmentioning
confidence: 99%
“…The development of Headstrong was underpinned by the Behaviour Change Wheel (BCW) [26]. We have used this theoretical foundation in other mental health programs [28],[29] to determine influences on pharmacists' and pharmacy staff behaviours as well as to design programs and services. The BCW was developed from frameworks of behaviour change and includes the behaviour system known as COM-B at the centre [26].…”
Section: Methodsmentioning
confidence: 99%
“…We also believe in the importance of donating resources such as volunteering time and fundraising for non-governmental, community-based mental health organizations. A significant pillar in our program of research, in which we consistently use mixed methods, focuses on the design, implementation, and evaluation of programs, such as Headstrong and the Bloom Program [29], to enhance community pharmacists' care of people with experience of mental illness and addictions. As part of this process, we attempt to understand the experiences of pharmacists and other pharmacy team members and people with lived experience of mental illness and addictions who use pharmacists' services.…”
Section: Methodsmentioning
confidence: 99%
“…A Canadian study demonstrated that pharmacy staff supported mental health consumers by providing follow-up care which focused on medication management and improving health service navigation and most study participants were using multiple psychotropic medications, few were living with SPMI (n=36; 17.9%). 32 33 Additionally, results from an Australian community-based, pharmacist-led medication support service for participants living with depression and anxiety were positive with significant improvements in relation to participants illness perceptions, medication satisfaction and medication adherence. 6 Our proposed Randomised Controlled Trial (RCT) builds and expands on this evidence to test the effectiveness of a person-centred, goal-oriented and flexible, pharmacist-led support service for people living with SPMI, with a specific focus on improving medication adherence and managing physical comorbidities.…”
Section: Background and Rationalementioning
confidence: 98%